INTEGRITAS ASN KPU SUMATERA UTARA DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH SUMATERA UTARA TAHUN 2018 - Rajab, Abd (Program Studi Ilmu Pemerintahan Universitas Muhammadiyah Buton, 2020)
Abstract: This study aims to find out how the attitude of the North Sumatra Provincial KPU ASN in carrying out an attitude of integrity includes aspects of professionalism, neutrality and national insight in organizing the Election of Governor and Deputy Governor of North Sumatra in 2018. This study uses qualitative research with synchronous science that tries to pay attention to the interrelationships between phenomena Election of the Governor and Deputy Governor of North Sumatra Province in 2018 with national and global realities related to the development of democratic life through the General Election event and the performance of the State Civil Apparatus (ASN) Secretariat of the Election Commission of the North Sumatra Province as the apparatus organizer in affection and cognition. The object of this research is ASN KPU North Sumatra Province's integrity and professionalism. While the subjects in this study consisted of 35 (thirty-five) staff in the General Election Commission (KPU). The conclusion of this research is the urgency of the research lies in improving the performance and professionalism of ASN, in a useful way, this research is useful to make the ASN figure as a civil service that is dedicated and provides maximum service to the general public.   keywords: integrity; nationalism insight; professionalism       Abstrak: Penelitian ini bertujuan untuk mengetahui bagaimana sikap ASN KPU Provinsi Sumatera Utara dalam menjalankan sikap integritas mencakup aspek profesionalisme, netralitas dan wawasan kebangsaan pada penyelenggaraan Pemilihan Gubernur dan Wakil Gubernur Sumatera Utara Tahun 2018. Penelitian ini menggunakan penelitian kualitatif dengan ilmu sinkronis yang mencoba memperhatikan keterkaitan antara fenomena lokal Pemlihan Gubernur dan Wakil Gubernur Provinsi Sumatera Utara tahun 2018 dengan realitas nasional maupun global terkait perkembangan kehidupaan demokrasi melalui ajang Pemilihan Umum dan kinerja Aparatur Sipil Negara (ASN) Sekretariat Komisi Pemilihan Umum Provinsi Sumatera Utara sebagai aparatur penyelenggara secara afeksi dan kognisi. Objek dalam penelitian ini adalah integritas dan profesional ASN KPU Provinsi Sumatera Utara.  Sedangkan subjek dalam penelitian ini terdiri dari Staf di Komisi Pemilihan Umum (KPU) sebanyak 35 (tiga puluh lima) orang. Kesimpulan dari penelitian ini adalah urgensi penelitian terletak pada peningkatan kinerja dan profesionalitas ASN, secara manfaat, penelitian ini bermanfaat untuk menjadikan sosok ASN sebagai aparatur sipil yang berdedikasi dan memberikan pelayanan maksimal kepada masyarakat umum.   kata kunci : Integritas; wawasan kebangsaan; profesionalisme